INTERIOR MISE-EN SCENE IN ASIAN HORROR FILM’S SETTINGS - Widyaevan, Dea Aulia; Wiguna, Iqbal Prabawa (Capture : Jurnal Seni Media Rekam, 2021)
Interior design is a process of conditioning a specific atmosphere, which relates to the concept of 'staging space.' As interior design is inherently designed to create an illusory world, the 'illusive, simulative' space can be used interchangeably with the real-imagined space of interior design and cinema. This article will examine three horror films to focus on how interior mise-en-scene is used to create a horror atmosphere. The films A Mother's Love, Tatami, and POB embodied semantic meanings into their spatial settings, serving as a projection of the characters; psyche, and story plots. A rhetorical visual method is used to interpret the relationship between spatial language, camera angle, character, and story plot. The research discovers that spatial language is an instrument of terror, as repeated patterns of liminal space, backlighting lights, and dream scene metaphors enhance the properties and camera angles to elicit an emotion of horror.